Multifidelity topology design of a maritime survey operation with UUVs - Morey, Danielle F.; Plate, Randall S.; Wakayama, Cherry Y.; Zabinsky, Zelda B. (Frontiers in Marine Science, 2024)
Advances in autonomous systems, maritime communications, and sensing technologies lead to increasing applications of unmanned underwater vehicles (UUVs). In this paper, we study a maritime survey operation topology design problem with UUVs that traverse an ocean environment and collect data from pre-specified sensors or locations. This maritime scenario is analyzed via several models and a simulation for the purpose of topology design for mission planning.We use a multi-fidelity approach to examine the trade-offs between different potential topology configurations of assigning UUVs to data collection sensors or locations. We develop three low-fidelity models that make simplifying assumptions. These models provide insight into design characteristics and allow for sensitivity analysis with low computational cost. They are used to down-select potential configuration designs for further evaluation using a high-fidelity simulation model. A high-fidelity simulation model removes many simplifying assumptions and predicts how a topology design would perform under more realistic conditions. It gathers detailed performance metrics at the expense of higher computational cost. Our study uses this multi-fidelity approach to demonstrate key trade-offs for topology design. The optimal design of UUVs depends on mission-specific goals.